Reasons people enjoy sexist humor and accept it as inoffensive. Issue 2 (14th March 2020) - Parrott, Scott; Hopp, Toby
ABSTRACT: An experiment examined factors that inform participants' enjoyment of anti-female humor and their acceptance of the humor as inoffensive. Participants ( n = 101) were exposed to sexist humor that was communicated by either (a) a male disparager, (b) a female disparager,  or (c) a disparager whose sex was not identified. A path model examined the contribution of four predictors – the experimental manipulation and audience members' hostile sexism, sex, and perceptions of social acceptance of the humor – in their reported personal acceptance and enjoyment of the insulting humor. The results suggested that men both found anti-female sexist humor more acceptable and enjoyed it more than women; that sexist humor was found to be more personally acceptable when communicated by a woman; that hostile sexism was positively associated with personal acceptance of sexist humor as inoffensive; and that perceived social acceptance was positively associated with personal acceptance of disparaging humor as inoffensive.